Business Strategy and Competitiveness in the Garment Sector of MetropolitanLima,Peru - Espinoza Shuña de Vizarreta, María del Pilar; Vargas-Merino, Jorge Alberto (LACCEI, 2024)
The present study aimed to determine the relationship between business strategy and competitiveness in the garment sector of Metropolitan Lima, Peru, in 2023. The study employed a quantitative approach, specifically a basic correlational design, non-experimental, and cross-sectional. Additionally, it had a sample of 80 managers, owners, and executives in the garment sector, using non-probabilistic convenience sampling. A questionnaire was utilized as the data collection instrument, consisting of 35 Likert scale questions. Data processing was carried out using SPSS version 29. Regarding the results, a very strong positive correlation of 79.9% was found between the investigated variables. In conclusion, it was determined that both business strategy and competitiveness are significantly related, given that the significance level is less than 0.05. Therefore, effective management of business strategies directly impacts the competitive capacity of organizations.